2019
DOI: 10.1080/0886022x.2019.1655451
|View full text |Cite
|
Sign up to set email alerts
|

Plasma triglyceride levels and central obesity predict the development of kidney injury in Chinese community older adults

Abstract: Objective: Despite the achievement of blood glucose, blood pressure targets, the risk for kidney injury remains high among older adults. This observational retrospective study investigated whether high TG or high WC contribute to this high residual risk for kidney injury. Methods: A total of 843 elderly from Dongli Community, Tianjin, China, we selected 666 individuals with a baseline estimated glomerular filtration rate (eGFR) 60 mL/min/1.73 m 2 and negative microalbuminuria completing a 3-year follow-up. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
4
12
1
1
Order By: Relevance
“…In fact, the findings on the relationship between serum lipids and CKD development are inconclusive. Our results are similar to the conclusions of previous studies that TG levels are related to kidney function, which were also confirmed in the elderly population in Cao’s research [ 30 ]. Interestingly, some reports have presented a contradictory conclusion that no association exists between TG and kidney function [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…In fact, the findings on the relationship between serum lipids and CKD development are inconclusive. Our results are similar to the conclusions of previous studies that TG levels are related to kidney function, which were also confirmed in the elderly population in Cao’s research [ 30 ]. Interestingly, some reports have presented a contradictory conclusion that no association exists between TG and kidney function [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have shown that central obesity has a higher risk of an elevated UACR than peripheral obesity, which may explain why the risk was higher in the South. 32 33 Moreover, the southern population had a lower average obesity rate than the northern population, making it easier for them to exceed obesity standards. Therefore, it is more dangerous to gain the same weight or WC as the northern population.…”
Section: Discussionmentioning
confidence: 99%
“…Central obesity is highly correlated with kidney injury [62,69]. It also has significant correlation with urinary incontinency.…”
Section: Health Impact Of Obesitymentioning
confidence: 99%